2015
DOI: 10.1093/mnras/stv2110
|View full text |Cite
|
Sign up to set email alerts
|

The integrated Sachs–Wolfe signal from BOSS superstructures

Abstract: Cosmic structures leave an imprint on the microwave background radiation through the integrated Sachs-Wolfe effect. We construct a template map of the linear signal using the SDSS-III Baryon Acoustic Oscillation Survey at redshift 0.43 < z < 0.65. We verify the imprint of this map on the Planck CMB temperature map at the 97% confidence level and show consistency with the density-temperature cross-correlation measurement. Using this ISW reconstruction as a template we investigate the presence of ISW sources and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 53 publications
2
40
1
Order By: Relevance
“…Foremost, Granett et al (2008) (Gr08, hereafter) defined a catalog of 50-50 significant super voids and superclusters using SDSS photo-z data. Using a BOSS DR12 spec-z galaxy catalogue, Granett et al (2015) reconstructed the average redshift space shape of the Gr08 super voids that were originally defined by photo-z tracers, finding an axis ratio R /R ⊥ ≈ 2.6 ± 0.4.…”
Section: Sdss Super Voids and Their Isw-like Effectmentioning
confidence: 99%
“…Foremost, Granett et al (2008) (Gr08, hereafter) defined a catalog of 50-50 significant super voids and superclusters using SDSS photo-z data. Using a BOSS DR12 spec-z galaxy catalogue, Granett et al (2015) reconstructed the average redshift space shape of the Gr08 super voids that were originally defined by photo-z tracers, finding an axis ratio R /R ⊥ ≈ 2.6 ± 0.4.…”
Section: Sdss Super Voids and Their Isw-like Effectmentioning
confidence: 99%
“…Another common approach in measuring the ISW signal is by stacking of voids and super-clusters. Similar to the cross-correlation method, studies using this approach have obtained detection significances ranging from low to moderate (Granett et al 2015;Kovács et al 2017), to 3σ or higher (Pápai et al 2011;Nadathur & Crittenden 2016;Cai et al 2017;Planck Collaboration et al 2016c). Interestingly, a number of these studies have reported a signal with a higher amplitude than expected based on ΛCDM predictions.…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of G08 is that their voids were found in a photometric redshift catalogue, with large redshift uncertainties compared to spectroscopic redshift samples. But the photometric redshift smearing may even help to detect very elongated structures along the line of sight, which may have the highest ISW signals (Granett, Kovács & Hawken 2015). Our goal in this study is therefore to conduct a similar analysis using the larger SDSS Data Release 12 (DR12) CMASS spectroscopic redshift sample, which covers the same redshift range (0.4 < z < 0.7) and the same volume as that of the DR6 photometric redshift sample in the North Galactic Cap (NGC) region.…”
Section: Introductionmentioning
confidence: 99%